KOMUNIKASI ORGANISASI DAN MANAJEMEN RELASI DALAM PERSPEKTIF HADIS - Istiqomah; Kurnia Syifa’ul Husnah; Fahmi Riady; Suraijiah; Rusdiana (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to analyze organizational communication and relationship management from the perspective of hadith and their relevance to the effectiveness of modern organizations. Organizational communication is an important element in the process of delivering information, coordinating work, making decisions, and building harmonious relationships among organizational members. Meanwhile, relationship management plays a role in establishing, maintaining, and strengthening relationships between organizations and both internal and external stakeholders. This study uses a qualitative descriptive method with a library research approach by examining various scientific literature, books, journals, and hadiths related to communication ethics and social relations in Islam. The results show that organizational communication from the perspective of hadith emphasizes the values of honesty (ṣidq), speaking good words or remaining silent, verification of information (tabayyun), mutual respect, and deliberation in decision-making. Relationship management in Islam is built upon the principles of brotherhood (ukhuwah), trustworthiness (amanah), cooperation, and maintaining good social relationships. The implementation of these hadith values can create effective communication, increase trust, minimize conflicts, and support the achievement of organizational goals optimally. Therefore, organizational communication and relationship management from the perspective of hadith have an important contribution in creating professional organizations that are also grounded in Islamic values.